EFL Students’ Perception on the Use of Spotify to Enhance English Pronunciation - Sari, Oktia Puspita; Syafryadin, Syafryadin; Damayanti, Indah (Journal of English Education and Teaching, 2025)
This study aimed to investigate students’ perceptions of using Spotify to enhance their English pronunciation. A quantitative descriptive approach was used, with data collected through a structured questionnaire distributed to 57 sixth-semester students of the English Education Study Program at the University of Bengkulu. The research applied two theoretical lenses: the Technology Acceptance Model (TAM) and sensory perception theory, to examine how students interact with Spotify as a pronunciation tool. The findings indicate that students generally had a positive perception of using Spotify in their learning. The majority believed that Spotify was useful, easy to use, and enjoyable, which encouraged repeated practice and exposure to native English pronunciation. Features like synchronized lyrics, audio looping, and various English accents were seen as highly supportive. Furthermore, sensory elements such as listening, reading lyrics, and app interaction contributed to learners’ engagement and pronunciation development. However, not all students responded the same way, suggesting that the tool's effectiveness depends on individual learning styles and preferences. While Spotify was considered a valuable supplementary resource, students did not view it as a complete replacement for formal instruction. Overall, this study supports the potential of integrating Spotify into EFL contexts to make pronunciation learning more accessible, flexible, and engaging.